The Influence of Marketing Literacy, Fear of Missing Out (FOMO), Social Class and Brand Awareness on Generation Z's Purchase Behavior with Consumer Satisfaction as a Mediating Variable - Nuranti, Barida Rakhma; Saputra, Viant Anggi; Utami, Zuchdiawati Luthfi; Putra, Reska Anggara (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the influence of marketing literacy, Fear of Missing Out (FOMO), social class, and brand awareness on Generation Z's purchase behavior with consumer satisfaction as a mediating variable. Using a quantitative approach with a causal design, data were collected through structured questionnaires from 203 Generation Z respondents in Yogyakarta who are active shoppers of fashion products. Data analysis used Partial Least Squares (PLS) based Structural Equation Modeling (SEM). The results show that the four independent variables have a positive and significant influence on purchase behavior with a coefficient of determination (R²) of 0.729. Brand awareness is the most dominant predictor (β = 0.369, p < 0.001), followed by marketing literacy (β = 0.303, p < 0.001), social class (β = 0.296, p < 0.001), and FOMO (β = 0.258, p < 0.001). Consumer satisfaction was proven to be a significant partial mediator with an R² of 0.683. These findings provide a theoretical contribution to the development of a Generation Z consumer behavior model and practical implications for fashion businesses in formulating effective marketing strategies.